Modelling analysis of earthquake impact on R.C Buildings in Baghdad using SAP200 / Manaf Raid Salman, Hasan Ali Abbas and Hasanain Muhammad Ghaltan - Raid Salman, Manaf; Ali Abbas, Hasan; Muhammad Ghaltan, Hasanain (Smart Manufacturing Research Institute (SMRI), 2023)
Most typical commercial reinforced concrete buildings in Iraq were designed using outdated building codes that did not consider horizontal seismic loads; they primarily focused on vertical loads. As a result, there is uncertainty regarding whether these conventional buildings can withstand recent earthquakes in Iraq. In this study, we created a three-dimensional finite element model using SAP2000 to represent scaled versions of typical multistory reinforced concrete commercial structures found in Iraqi cities. The primary objective was to investigate how these structures respond to seismic events, particularly the Ali Al-Gharbee earthquake that struck Maysan Province in southern Iraq in 2012, with a magnitude of Mw=4.9 and PGA=104.151 cm/sec2 as the input ground motion. Our findings indicate that typical multistory reinforced concrete commercial buildings in Iraq can safely withstand earthquakes. However, when the magnitude increases to approximately Mw=5.2 (PGA=156 cm/sec2), some members may experience cracking and exceed allowable drift limits. If the magnitude reaches about Mw=6 (PGA=208 cm/sec2), these buildings may experience complete failure.